Effects of methylphenidate on children with attention deficit hyperactivity disorder: a study using clinical and multimodal approaches including go/no-go task and functional near-infrared spectroscopy - Shen, Fang; Zhou, Hui (Frontiers in Pharmacology, 2025)
ObjectiveThis study aims to provide an objective evaluation of the therapeutic effects of methylphenidate (MPH) in children with attention deficit hyperactivity disorder (ADHD) by integrating clinical assessments, the go/no-go task, and functional near-infrared spectroscopy (fNIRS).MethodsThis study employed a two-part design. First, a cross-sectional comparison was conducted between 36 children with ADHD and 12 typically developing controls (TDC) to establish baseline neurocognitive and functional differences. Second, a pre-post intervention design was used to evaluate the effects of a 6-month MPH treatment on the 36 children with ADHD. All participants underwent clinical assessments, including the Swanson, Nolan, and Pelham IV Rating Scale (SNAP-IV) and the Weiss Functional Impairment Rating Scale (WFIRS), a go/no-go task, and fNIRS to measure average oxygenated hemoglobin (Δavg oxy-Hb) changes in targeted brain regions, including the medial prefrontal cortex (mPFC), dorsolateral prefrontal cortex (DLPFC), and temporal lobe (TL).ResultsThe findings of the present study revealed that, at baseline, children with ADHD had significantly higher scores on the SNAP-IV and WFIRS than the TDC group. On the go/no-go task, accuracy for both go and no-go trials was significantly lower in the ADHD group than in the TDC group. Furthermore, fNIRS data indicated that the ADHD group had significantly lower Δavg oxy-Hb levels than the TDC group in the bilateral mPFC, right DLPFC, and bilateral TL. After 6 months of MPH treatment, children with ADHD showed significant reductions in SNAP-IV and WFIRS scores. Concurrently, they showed significantly increased accuracy on both go and no-go trials, along with significantly decreased reaction times on go trials. Furthermore, Δavg oxy-Hb levels increased significantly in the right mPFC.ConclusionOur findings suggest that activation in the right mPFC is a viable objective neurofunctional biomarker for monitoring MPH treatment response using fNIRS. Concurrently, a multimodal assessment strategy integrating clinical evaluations, neuropsychological testing (go/no-go task), and fNIRS holds significant promise as a robust method for objectively determining the therapeutic efficacy of MPH in pediatric ADHD.